If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + ax = 0 Reorder the terms: ax + 5y = 0 Solving ax + 5y = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-5y' to each side of the equation. ax + 5y + -5y = 0 + -5y Combine like terms: 5y + -5y = 0 ax + 0 = 0 + -5y ax = 0 + -5y Remove the zero: ax = -5y Divide each side by 'x'. a = -5x-1y Simplifying a = -5x-1y
| x/12=2/8 | | -4x+by=6 | | 8-8x-4=-37+3x-14 | | 2.1y+37.8=7.4y+6 | | -7v+1=-5v+1 | | a+5y=0 | | 4x^2-12=4 | | 6x^3-13x^2-28=0 | | f(-2)givenf(x)=3x^2+5x+12 | | -16+2x=4x-16-12 | | x+29=-5x+5 | | x+29=-5a+5 | | -2(x)=3x^2+5x+12 | | 10=-16t^2+8t+48 | | -2/9*1/5= | | r(p)=-6p^2+42000p | | (3*5+x)=(5+x)3 | | a/-9=-6 | | (3*5+x)=(5+x*3) | | 2.9=y-63 | | (x-2)(x+1)+(x-2)(x+8)=0 | | (9-v)(3v-5)=0 | | 3=5+w | | 3(5+x)=(5+x)3 | | 2(3x-2)-4x=2 | | 25k=15k+8 | | 4v+7=2v-5 | | 64=5w+14 | | (2x)+(3x+11)+(7x+13)=180 | | 16=-6+n | | 11=-5/6x | | 7x+2=32+x |